Evidence from Rwanda showed that consumption of iron biofortified beans had a positive effect on cognitive performance of young women - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Published evidence on the nutritional impact of iron-biofortified crops offers a road map for policymakers to consider. Within the context of an RCT in Rwanda, one group of female college students consumed iron biofortified beans and another group consumed conventional beans. Results showed that the consumption of iron biofortified beans positively affected the cognitive performance of the young women in the treatment group. Iron biofortified beans were developed in close collaboration between HarvestPlus, CIAT and the Rwanda Agricultural Board.